Evaluation and management of the patient with a failed midurethral synthetic sling - Gormley, E. Ann (Canadian Urological Association Journal, 2012)
While most women will do well following placement of a midurethral sling (MUS), a substantial minority do experience surgical failure. There are several risk factors that can help identify a patient at higher risk for failure, including body mass index greater than 25 kg/m2, mixed incontinence, previous continence surgery, intrinsic sphincter deficiency, and diabetes. At the present time, there is no evidence-based guidance for which intervention to use following failure. Careful evaluation of patient characteristics will help guide subsequent management.